Anomalous Zenith Total Delays for an Insular Tropical Location: The Tahiti Island Case - Fangzhao Zhang; Peng Feng; Guochang Xu; Jean-Pierre Barriot (Remote Sensing, 2022)
The weighted mean temperature of the troposphere, Tm, is a key parameter in GNSS meteorology. It can be routinely derived based on meteorological data from radiosonde (RS) or numerical weather models. Alternatively, it can be also derived through a least-squares model of the ratio between the precipitable water vapor from RS data and the zenith wet delay estimates from GNSS measurement in the precise point positioning mode. In this last case, we found anomalous Tm values for the remote sub-tropical humid location of the Tahiti Island in the South Pacific Ocean and traced these anomalous values to anomalous zenith total delays (ZTD) that seem to have an accuracy poorer by one order of magnitude than the claimed accuracy of ZTD delays from worldwide databases. The possible causes of these discrepancies are discussed.